The willingness of private-sector doctors to manage public-sector HIV/AIDS patients in the eThekwini metropolitan region of KwaZulu-Natal - Panjasaram Naidoo; Champaklal C. Jinabhai; Myra Taylor (AOSIS, 2010)
Background: South Africa is severely affected by the AIDS pandemic and this has resulted in an already under-resourced public sector being placed under further stress, while there remains a vibrant private sector. To address some of the resource and personnel shortages facing the public sector in South Africa, partnerships between the public and private sectors are slowly being forged. However, little is known about the willingness of private-sector doctors in the eThekwini Metropolitan (Metro) region of KwaZulu-Natal, South Africa to manage public-sector HIV and AIDS patients. Objectives: To gauge the willingness of private-sector doctor to manage public-sector HIV and AIDS patients and to describe factors that may infuence their responses. Method: A descriptive cross-sectional study was undertaken among private-sector doctors, both general practitioners (GPs) and specialists, working in the eThekwini Metro, using an anonymous, structured questionnaire to investigate their willingness to manage public-sector HIV and AIDS patients and the factors associated with their responses. Chi-square and independent t-tests were used to evaluate associations. Odds ratios were determined using a binary logistic regression model. A p value < 0.05 was considered statistically significant. Results: Most of the doctors were male GPs aged 30-50 years who had been in practice for more than 10 years. Of these, 133 (77.8%) were willing to manage public-sector HIV and AIDS patients, with 105 (78.9%) reporting adequate knowledge, 99 (74.4%) adequate time, and 83 (62.4%) adequate infrastructure. Of the 38 (22.2%) that were unwilling to manage these patients, more than 80% cited a lack of time, knowledge and infrastructure to manage them. Another reason cited by five doctors (3.8%) who were unwilling, was the distance from public-sector facilities. Of the 33 specialist doctors, 14 (42.4%) indicated that they would not be willing to manage public-sector HIV and AIDS patients, compared with only 24 (17.4%) of the 138 GPs (p < 0.01). Conclusion: Many private-sector doctors are willing to manage public-sector HIV and AIDS patients in the eThekwini Metro, potentially removing some of the current burden on the public health sector.